The Perception Justice Effect, Recovery Disconfirmation, And Recovery Satisfaction on Positive Word of Mouth Behavior After Failure Delivery Over Fast Food Restaurant Service - Sri Rahayu Ningsih; Rhian Indradewa; Tantri Yanuar Rahmat Syah; Diana Fajarwati (Penerbit Kemala Indonesia, 2021)
This study aims to analyse the effect of perception of justice, recovery disconfirmation, recovery satisfaction in positive word of mouth behaviour after failure delivery over fast food restaurants service. Fast food restaurant customers were chosen as the object of the current study, the products by fast food restaurant have specialties taste. The products by this restaurant have won customers’ trust which is known as a high-quality brand. In this study, the analytical model by using Structural Equation Modelling and SPSS 25 Program was proposed to process the data. The results show failure service fast food restaurant on perception effect of customer justice on PWOM through mediators such as recovery disconfirmation, inconsistency between expectations for recovery satisfaction and positive word of mouth. Post-recovery satisfaction by forming a bond between the customer and the service provider. The addressing service failures successfully is essential to a reputation for delivering a quality service and allows industry practitioners to maintain strong relationships with customers and, subsequently, earn the greater market share enjoyed by high-quality organizations with reliability test 0.971. Here, the findings suggest that quality professional service should aim to maximize the influence of fast-food restaurant customers’ perception of justice on their post-complaint behaviour through the development of dual mediators: recovery disconfirmation and recovery satisfaction. Thus, can help quality professionals influence restaurant customers’ post-complaint behaviour in a positive way.